2022
DOI: 10.3389/fpubh.2022.842665
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Abnormally Hot Temperature and the Demand for Commercial Health Insurance

Abstract: Using the China Health and Retirement Longitudinal Study, this paper studies the impact of abnormal hot temperature on residents' demand for commercial health insurance. The results show that for every 1°F rise in abnormal temperature, the probability of people buying commercial health insurance increased by 6%. Furthermore, the abnormal hot temperature has a more significant impact on the commercial health insurance demand of women, residents in the South and residents in the East. Channel analysis shows that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The research results show that age, education level and income significantly promoted residents’ demand for commercial health insurance, but gender and marital status had no significant impact on the demand for commercial health insurance. Zhong et al (2022) [ 19 ] analyzed and studied the data of the China Health and Retirement Longitudinal Study (CHARLS) in 2011, 2013 and 2015. By constructing a panel logit model, it was concluded that age and marital status of residents were significantly negatively correlated with the demand for commercial medical insurance, while gender and education level of residents were significantly positively correlated with the demand for commercial medical insurance.…”
Section: Relevant Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…The research results show that age, education level and income significantly promoted residents’ demand for commercial health insurance, but gender and marital status had no significant impact on the demand for commercial health insurance. Zhong et al (2022) [ 19 ] analyzed and studied the data of the China Health and Retirement Longitudinal Study (CHARLS) in 2011, 2013 and 2015. By constructing a panel logit model, it was concluded that age and marital status of residents were significantly negatively correlated with the demand for commercial medical insurance, while gender and education level of residents were significantly positively correlated with the demand for commercial medical insurance.…”
Section: Relevant Literature Reviewmentioning
confidence: 99%
“…On the other hand, in the long term, due to the increasing proportion of the total dependent population, the elderly population or the number of minors seriously exceed the standard, resulting in excessive family economic burden and decreased purchasing power, thus reducing the demand for commercial health insurance, that is, the age characteristics of residents have a negative effect on the demand for commercial health insurance [ 19 ]. Based on the above discussion, this paper proposes the following hypothesis:…”
Section: Theoretical Analysis and Research Hypothesismentioning
confidence: 99%
See 2 more Smart Citations
“…One of the current problems in urban areas is heavy rain, which can easily flood drainage systems that lack sufficient capacity because of increasing urbanization and climate change [3,4]. Extremely high temperatures are becoming increasingly common in cities, with a negative impact on residents [5]. Rainwater retained by green infrastructure provides a measurable effect, in the form of cooling the surrounding area and building interiors [6,7].…”
Section: Introductionmentioning
confidence: 99%